Medial Collateral Ligament Release Facilitates Exposure in Revision Total Knee Arthroplasty - Bou Monsef, Jad; Boettner, Friedrich (The Journal of Knee Surgery Reports, 2015)
Incidence of revision total knee arthroplasty is growing. Revision surgery aims at preserving the collateral ligaments to minimize implant constraint and stress on the implant-cement-bone interface. Exposure in the stiff knee can be challenging as a result of loss of soft tissue elasticity and capsular scarring brought on by multiple surgeries. If a quadriceps snip does not provide adequate visualization a quadriceps turndown or a tibial tubercle osteotomy is recommended to improve exposure. Such extensile approaches have various limitations and might risk compromising the extensor mechanism, recovery time, bone fixation, or wound healing. The current case report describes a novel technique to combine a quadriceps snip with cutting the medial collateral ligament to gain exposure. While patients require a hinged implant, the integrity of the extensor mechanism is preserved. This allows for immediate active and passive range of motion and places this approach at an advantage over a quadriceps turndown or tibial tubercle osteotomy.
Keywords: exposure; revision total knee arthroplasty; orthopedic surgery; knee arthroplasty